Refocusing Prevention Practices: From Risk-Based Towards Social Developmental Measures - Sorinmade, Ibukun (Université d'Ottawa / University of Ottawa, 2012)
In exploring current responses to crime, particularly youth involvement in gangs, this thesis examines two approaches: Crime Prevention through Social Development (CPSD) and risk-based prevention. The former is associated with the provision of socially-designed measures to address and eliminate the risk factor associated with persistent offending. The latter, however, refers to the implementation of risk management and statistical assessment to manage the risk factor associated with persistent offending. In light of these two approaches, this thesis examines a debate which purported that crime prevention practices has wholly shifted away from an emphasis on CPSD towards risk-based prevention. This thesis also examines the opposing debate which explains that CPSD and risk-based prevention have emerged into a balanced approach. Taking into account 19 youth gang prevention projects in Canada, the above debates are investigated. Drawing from the analysed project, this thesis concludes that, the crime prevention practices of the analyzed projects significantly rely on risk-based prevention. As a result, the approaches of CPSD still exist in rhetoric and in practice however, its influence on crime prevention initiatives is very limited. Hence, current approaches neither reflect a total shift away from CPSD nor a balanced approach.
Keywords: Risk factors; Crime prevention through social development; Risk-based prevention